Comprehensive Cyber Risk Governance Frameworks and Implementation Methodologies for AI-Augmented Enterprises: Architectural Considerations, Standards Alignment, Case Studies, and Future Directions - Olomola, Abiola; Shobukola, Oluwatosin (International Journal of Scientific Research and Management (IJSRM), 2023)
The integration of artificial intelligence into enterprise operations has transformed cyber risk management, necessitating the development of comprehensive governance frameworks tailored to AI-augmented environments across on-premise, cloud, and hybrid infrastructures. This work ex- amines the unique risk profiles introduced by AI systems, including adversarial attacks, data poisoning, and ethical challenges such as algorithmic bias and transparency. It highlights the critical role of established standards like NIST and ISO in structuring adaptable, resilient gover- nance models that incorporate proactive risk management, continuous monitoring, and AI-driven security automation. Architectural considerations for diverse deployment scenarios are explored, emphasizing identity and access management, data security, network segmentation, and model gov- ernance. The discussion extends to regulatory evolution, sector-specific implementations, and the importance of organizational culture, training, and leadership engagement in sustaining effective cyber risk governance. Emerging technologies such as zero trust architectures, federated learning, and post-quantum security are analyzed for their impact on future governance strategies. The synthesis of technical, ethical, and procedural dimensions provides a multidisciplinary approach to securing AI-enabled enterprises, ensuring transparency, accountability, and trust while supporting innovation and compliance in an evolving threat landscape.